Pilot study: incorporation of pharmacogenetic testing in medication therapy management services. (November 2014) - Haga, Susanne B; Allen LaPointe, Nancy M; Moaddeb, Jivan; Mills, Rachel; Patel, Mahesh; Kraus, William E
Aim: To describe the rationale and design of a pilot study evaluating the integration of pharmacogenetic (PGx) testing into pharmacist-delivered medication therapy management (MTM).Study rationale: Clinical delivery approaches of PGx testing involving pharmacists may overcome barriers of limited physician knowledge about and experience with testing.Study design: We will assess the addition of PGx testing to MTM services for cardiology patients taking three or more medications including simvastatin or clopidogrel. We will measure the impact of MTM plus PGx testing on drug/dose adjustment and clinical outcomes. Factors associated with delivery, such as time to prepare and conduct MTM and consult with physicians will be recorded. Additionally, patient interest and satisfaction will be measured.Anticipated results: We anticipate that PGx testing can be practically integrated into standard a MTM service, providing a viable delivery model for testing.Conclusion: Given the lack of evidence of an effective PGx delivery models, this study will provide preliminary evidence regarding a pharmacist-delivered approach.